Penerapan Metode Demonstrasi Pada Pembelajaran Fisika Materi Kinematika Untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA/MA - Nurul Nur Afifah; Martha Loupatty; Helga C. Antonia Silubun (Musamus Journal of Science Education, 2020)
This research is a classroom action research carried out in two cycles where each cycle is carried out in four languages ​​namely: planning, implementation, observation and reflection. The subjects in this study were all students of class X Annajah Yamra Merauke who won 31 people. Research in Odd Semesters of Academic Year 2017/2018. The data obtained were analyzed using quantitative data and the completeness of learning outcomes, teacher and student observation sheets were analyzed using conversions. The results obtained show that learning methods can improve student learning outcomes in class X MA Annajah Yamra Merauke. The increase in average physics learning outcomes from Prasiklus 44.6 to 67.3 in Cycle I and increased to 77.4 in Cycle II. As for the completeness of learning outcomes from Prasiklus namely 12% to 58% in Cycle I and increased to 87% in Cycle II. Increased student activity in the high category in cycle I to cycle II by 35% to 61% and the very high category by 26%. Teacher activity is in the high category of cycle I to cycle II by 65% ​​to 5% and very high category by 95%.